2004
DOI: 10.1007/s00431-004-1448-3
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of erythrocyte transfusion in preterm infants

Abstract: the data suggest that although a red cell transfusion of 10 ml/kg may marginally improve peripheral perfusion, it does not influence cardiac output and arterial blood pressure in normotensive preterm infants. It may, however, cause a transient decrease in oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Pulmonary vasodilatation in the early neonatal period may also be insufficient to compensate the increased blood viscosity after transfusion, resulting in pulmonary hypertension and a fall in pulmonary blood flow [32,33] . In this study, no decrease in oxygen saturation was noted and no adjustment in the mean airway pressure was necessary during or immediately after transfusion, suggesting a lower risk of altered pulmonary mechanics when transfusion is given for the correction of a true anemia rather than for the automatic replacement of blood losses [11] . A significant decrease in the oxygenation index was observed 48 h following transfusion, which confirmed the short-term improvements in oxygenation suggested by James et al [10] .…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Pulmonary vasodilatation in the early neonatal period may also be insufficient to compensate the increased blood viscosity after transfusion, resulting in pulmonary hypertension and a fall in pulmonary blood flow [32,33] . In this study, no decrease in oxygen saturation was noted and no adjustment in the mean airway pressure was necessary during or immediately after transfusion, suggesting a lower risk of altered pulmonary mechanics when transfusion is given for the correction of a true anemia rather than for the automatic replacement of blood losses [11] . A significant decrease in the oxygenation index was observed 48 h following transfusion, which confirmed the short-term improvements in oxygenation suggested by James et al [10] .…”
Section: Discussionmentioning
confidence: 89%
“…Measurements of cardiac output and blood pressure have been the main tools to assess the changes in systemic hemodynamics with transfusion. Using echocardiography, Leipälä et al [11] observed no variation in LV performance indexes 1 h following a 10 ml/kg packed donor red cell transfusion in very preterm infants during the first days after birth. The marked difference in the degree of anemia between the study of Leipälä et al [11] and our own probably explains the higher LV output of the anemic infants in our population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations